Diversities between pediatric extra-pulmonary and pulmonary tuberculosis: a warning sign for the future - ilker devrim; Hüseyin Aktürk; Hüseyin Aktürk; Nuri Bayram; Nuri Bayram; Hurşit Apa; Hurşit Apa; Şener Tulumoğlu; Şener Tulumoğlu; Fatma Devrim; Fatma Devrim; Tulin Erdem; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Tuberculosis(TB) remains a major global health problem. The childhood tuberculosis has some unique features different which makes the diagnosis more complicated. We described the epidemiologic, clinical and microbiologic features of children with extrapulmonary and pulmonary TB. Methods:  The data of the patients <17 years with active TB were collected and compared  in pulmonary(PTB) and extrapulmonary TB(EXPTB) patients.Results: A total of 128 cases were included. Fourty two cases occurred in children were < 5 years of age; 41 cases between 6-10 years and  45  cases > 10 years. PTB was present in 75.0% of the cases and  EXPTB was present in 25% of cases. There was no significant difference  between the EXPTB and PTB  by means of distribution of  age groups(p=0,201). The rate of patients free of  constitutional symptoms were significantly higher in EXPTB compared to PTB(p=0.000). There was no significant difference between EXPTB and PTB by means of sources detection(p=0.069). Conclusion : TB is still a major public health problem. EXPTB has an insidious  and silent onset without any constitutional symptoms and microbiological confirmation plus the adult source could not be found mostly. Thus detection of the adult source is mandatory for controlling the TB disease in children